2017
DOI: 10.1037/pag0000171
|View full text |Cite
|
Sign up to set email alerts
|

Younger and older adults’ associative memory for social information: The role of information importance.

Abstract: The ability to associate items in memory is critical for social interactions. Older adults show deficits in remembering associative information, but can sometimes remember high-value information. In two experiments, younger and older participants studied faces, names, and occupations that were of differing social value. There were no age differences in the recall of important information in Experiment 1, but age differences were present for less important information. In Experiment 2, when younger adults’ enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
6
24
0
Order By: Relevance
“…In both experiments, the associative recognition accuracy of both groups increased given task experience. This is similar to prior work suggesting that older adults benefit from prior successful task performance (Geraci & Miller, 2013; Hargis & Castel, 2017; Kilb & Naveh-Benjamin, 2011), and suggests that repeated study and retrieval of associative information regarding medication interactions can benefit overall recall of important pairs of items, even when there are interfering connections among medications. Additionally, the information was tested via associative recognition in which there were three answer choices.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In both experiments, the associative recognition accuracy of both groups increased given task experience. This is similar to prior work suggesting that older adults benefit from prior successful task performance (Geraci & Miller, 2013; Hargis & Castel, 2017; Kilb & Naveh-Benjamin, 2011), and suggests that repeated study and retrieval of associative information regarding medication interactions can benefit overall recall of important pairs of items, even when there are interfering connections among medications. Additionally, the information was tested via associative recognition in which there were three answer choices.…”
Section: Discussionsupporting
confidence: 85%
“…The associative deficit hypothesis suggests that the association of items in memory is detrimentally affected in older age (Naveh-Benjamin, 2000). This deficit is pervasive and present in various memory recall tasks, including remembering word-nonword pairs (Naveh-Benjamin, 2000), pairs of pictures (Naveh-Benjamin, Hussain, Guez, & Bar-On, 2003), and name-face pairs (Naveh-Benjamin, Guez, Kilb, & Reedy, 2004; though this can be affected by the value of the information and reduced with repeated testing, see Hargis & Castel, 2017).…”
mentioning
confidence: 99%
“…Such selectivity is emphasized by participants' study decisions in Experiment 2, with higher magnitudes receiving more study visits (and thus more total study time) despite equivalent study time per visit with lower magnitudes. As such, these results add further evidence that participants are effective in prioritizing important information, consistent with a large body of work demonstrating preserved selectivity with various materials like unrelated word pairs (Ariel et al, 2015), name-face pairs (Hargis & Castel, 2017), medication side effects (Hargis & Castel, 2018), and item-location pairs (Siegel & Castel, 2018b), and under varying degrees of cognitive ability, like healthy aging (Castel et al, 2002;Hayes et al, 2013;Siegel & Castel, 2018a), Alzheimer's disease (Castel et al, 2009), attention-deficit hyperactivity disorder (Castel et al, 2011), and different working memory capacities (Griffin, Benjamin, Sahakyan, & Stanley, 2019;Middlebrooks et al, 2017;Miller, Gross, & Unsworth, 2019;Robison & Unsworth, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…It has been observed that the recreation of the future is more likely to be performed in the third person rather than from a first-person perspective ( D’Argembeau and Van der Linden, 2004 , 2006 ). In addition, in the current context of pandemic, social content can be perceived as high-value information or more important than personal content ( Hargis and Castel, 2017 ). Therefore, we expect a better recall of social than of personal imagined future events.…”
Section: Introductionmentioning
confidence: 99%